Analisis Kebutuhan (Needs Analysis) untuk Pembelajaran Bahasa Arab Pariwisata: Studi Literatur - Irfan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study analyzes the need for Arabic language education in the tourism sector, focusing on teaching Arabic for specific purposes within the context of halal tourism. Based on a literature review, the findings indicate that the skills required include verbal communication abilities, mastery of tourism-related vocabulary, as well as an understanding of cultural nuances and social interactions with Arabic-speaking tourists. The main challenge identified is the dialectal differences among Arab countries, which can hinder effective communication. This study recommends the use of Modern Standard Arabic (MSA) as the standard for Arabic language teaching in the tourism sector, as well as the implementation of situational-based methods and digital technology to enhance communication skills. The limitation of this study lies in its reliance on literature review, which does not involve empirical data from the field, making the results theoretical and not fully reflective of the real-world dynamics in the tourism sector. Further research involving interviews with practitioners in the tourism industry could provide a deeper understanding of the challenges and needs for Arabic language education in this context.